A composition for optical lens material with high refractive index and low thermal expansion coefficient
By using a combination of cyclic sulfur compounds and compounds with specific structures, optical lens materials with high refractive index and low coefficient of thermal expansion are prepared, which solves the problem that existing materials cannot meet the demand of high-end markets and achieves high performance and low cost of the materials.
Patent Information
- Application Number
- CN202211609334.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The existing plastic lens materials have a low refractive index and a high thermal expansion coefficient, which cannot meet the high-end market's demand for high refractive index and low thermal expansion coefficient.
Using a composition of a cyclic sulfur compound and a compound having two or more active hydrogens and a number of methylene groups in a continuous fat chain is ≤2, an optical lens material with a refractive index between 1.60 and 1.75 and a linear expansion coefficient between 25 and 50×10-6/℃ was prepared by adjusting the component ratio and adding additives such as isocyanate.
It achieves a balance between high refractive index and low thermal expansion coefficient, the material size is more stable, the design is more flexible, and the cost is reduced, and it is suitable for higher-end optical lens materials.
Smart Images

Figure BDA0003993811720000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of optical materials, and in particular provides a composition for optical lens materials with high refractive index and low thermal expansion coefficient. Background Art
[0002] Optical plastics have many advantages. They can be mass-produced, reducing manufacturing costs; they can be designed into very complex shapes; they have low density, so they are lightweight; compared to the fragility of glass, they have good impact resistance; optical plastics have high transmittance, and their spectral absorption in the ultraviolet and infrared regions is different from that of glass, and can be adjusted through additives; optical surfaces and positioning surfaces can be pressed out at the same time, reducing system assembly costs; and parts have higher quality consistency.
[0003] There are more than ten kinds of plastic lens materials on the market, and their refractive index is relatively low, and the linear expansion coefficient is basically between 70 and 100×10 -6 ℃ -1 The details are shown in the following table:
[0004] Category Nd Vd <![CDATA[Coefficient of linear expansion * 10 -6 / °C]]> Polymethyl Methacrylate PMMA 1.491 57.2 83 Polystyrene PS 1.59-1.610 30.8 65-67 Polycarbonate PC 1.586 34 65.3-70 Cyclic Olefin Copolymer COC 1.535 56 60-70 Cyclic Olefin Polymer (COP) 1.525 55.8 70
[0005] The higher the thermal expansion coefficient of the material, the more the product's use conditions will be restricted by the temperature. Generally speaking, the maximum continuous operating temperature of plastic optical parts should not be higher than 80-120℃.
[0006] However, the demand of the high-end market is high refractive index and low thermal expansion coefficient. The existing plastic lens materials can no longer meet the above requirements. Therefore, there is an urgent need for an optical lens material with high refractive index and low thermal expansion coefficient. Summary of the invention
[0007] The present invention aims at the many deficiencies of the existing sulfur-containing optical material composition, and provides a composition for optical lens material with high refractive index and low thermal expansion coefficient. The composition is composed of an episulfide compound, a compound with more than 2 active hydrogens, and a continuous aliphatic chain methylene number ≤ 2. The refractive index of the optical lens material prepared by the composition can reach 1.60 to 1.75, which is suitable for higher-end optical lens materials; the linear expansion coefficient is between 25 and 50×10 -6 / ℃, the material's dimensions are more stable, the design is more flexible, and the cost is reduced.
[0008] The biggest difference between the present invention and the prior art is that the present invention adopts for the first time a combination of an episulfide compound and a compound having more than 2 active hydrogen atoms and a continuous aliphatic chain with a methylene number of ≤2. The episulfide compound has a high sulfur content, and its introduction can improve the refractive index and Abbe number of the material, meeting the market's high refractive index requirements; and the compound having more than 2 active hydrogen atoms and a continuous aliphatic chain with a methylene number of ≤2, wherein more than 2 active hydrogen atoms meet the requirements of high crosslinking degree, good dimensional stability, and a continuous methylene number of ≤2, meeting the requirements of high glass transition temperature, and achieving a low thermal expansion coefficient in a wide temperature range. The combination of the two can meet the requirements of the high refractive index and low thermal expansion coefficient in the high-end market.
[0009] The specific technical solution of this application is:
[0010] A composition for an optical lens material with a high refractive index and a low thermal expansion coefficient, the components of which are as follows by weight: component A: 50 to 100 parts of an episulfide compound; component B: 0.001 to 30 parts of a compound having more than 2 active hydrogen atoms and a continuous aliphatic chain with a methylene number of ≤2;
[0011] Preferably, the above composition further contains component C: 0-20 parts of isocyanate;
[0012] Most preferably, component A is 65-90 parts; component B is 1-20 parts; and component C is 4-16 parts.
[0013] Among the above components, the episulfide compound component A is selected from one or more of bis(β-epithiopropyl) sulfide, bis(β-epithiopropyl) disulfide, bis(β-epithiopropyl) trisulfide, bis(β-epithiopropylthio) methane, 1,2-bis(β-epithiopropylthio) ethane, 1,3-bis(β-epithiopropylthio) propane, 1,4-bis(β-epithiopropylthio) butane, and bis(β-epithiopropylthioethyl) sulfide.
[0014] The compound component B having more than two active hydrogen atoms and the number of continuous aliphatic chain methylene groups ≤2 is selected from one or more of 1,3-adamantanediol, 3-amino-1-adamantanol, 3-aminocyclohexanol, 1-(aminomethyl)cyclohexanemethanol, bicyclo[2.2.1]heptane-2,6-dithiol, (2-mercaptoethyl)cyclohexanethiol, 1,4-dithiane-2,5-dithiol, 1,4-dithiane-2,5-dimethylthiol, 1,6-dimercaptohexane, 2,2'-thiodiethanethiol, 2,3-bis(2-mercaptoethylthio)-3-propyl-1-thiol, and pentaerythritol tetrakis(3-mercaptopropionic acid) ester.
[0015] The isocyanate component C is selected from one or more of 4,4-dicyclohexylmethane diisocyanate, norbornane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, methylenebiscyclohexyl diisocyanate and 1,4-cyclohexane dimethyl diisocyanate.
[0016] Compared with the prior art, the present application defines component B as a component containing more than 2 active hydrogens and the number of continuous aliphatic chain methylene groups ≤ 2. This compound contains more than 2 active hydrogens, so that it is either a rigid structure or multifunctional, thereby meeting the requirements of high crosslinking degree and high glass transition temperature, Tg is above 120°C, and the final sample has good dimensional stability, and the processing temperature can be increased to 160°C. The thermal expansion coefficient is significantly reduced by testing to 25-50×10 -6 / ℃, filling the gap of new performance advantages of low expansion coefficient in the field of high-refractive optical materials, and the above-mentioned component A episulfide compound itself has a relatively high sulfur content, which gives the material a high-refractive property. The above combination of the two can obtain a material with both properties.
[0017] Among them, the most preferred component A is selected from one or two of bis(β-epithiopropyl) sulfide and bis(β-epithiopropyl) disulfide; component B is selected from one or more of 3-amino-1-adamantanol, 1,4-dithiane-2,5-dimethylthiol, and 2,3-dithio(2-yl)-1-propanethiol; and component C is selected from one or more of norbornane diisocyanate and isophorone diisocyanate.
[0018] The other components are conventional components in the art. When preparing optical material products, other additives such as blue or red agents may be added as needed. The inventors give the following examples:
[0019] The raw materials may also include:
[0020] The initiator is selected from one or more of tetrabutylammonium bromide, tetrabutylphosphonium bromide, and triphenylphosphine, more preferably tetrabutylphosphonium bromide;
[0021] The ultraviolet absorber is selected from one or more of UV-326, UV-327, UV-329, and UV-541, and more preferably UV-329;
[0022] The phosphate release agent is selected from one or more of dibutyl phosphate and polyoxyethylene ether phosphate;
[0023] Blue agent and red agent; the concentration of the blue agent is 3ppm-3.5ppm; the concentration of the red agent is 1ppm-2ppm. The above components can be added in appropriate amounts according to the performance requirements of the optical material, and the inventor will not elaborate on them.
[0024] The present application also provides a method for preparing the above-mentioned optical lens material with high refractive index and low thermal expansion coefficient, comprising the following steps:
[0025] a) mixing isocyanate, a compound having more than 2 active hydrogen atoms and a continuous fatty chain methylene group number of ≤2, an initiator, an ultraviolet absorber, a release agent, a blue agent and a red agent for the first time to obtain a prepolymer 1;
[0026] The main reason for adopting the above mixing method is that the initiator, ultraviolet absorber, release agent, blue agent and red agent are better dissolved in isocyanate than in episulfide compound, which reduces the time required for dissolution and further reduces the time of the whole reaction;
[0027] b) mixing the prepolymer 1 obtained in step a) with the episulfide compound for a second time to obtain a reaction mixture 2; the mixing temperature is 0° C.-15° C., the mixing time is 30 min-60 min, and vacuum degassing is performed for 20 min-40 min;
[0028] The above methods can remove air and moisture in the prepolymer, and no bubbles will be generated in the cured lens. If the temperature is not well controlled, the initiator will increase the viscosity of the prepolymer, which is not conducive to the subsequent sample pouring, so temperature and time control are required.
[0029] The mixture was filtered and cast using a polytetrafluoroethylene filter membrane commonly used in the art, and the cast sample was subjected to primary and secondary curing.
[0030] The heating program of the first curing is as follows: the initial temperature is 15-20°C, kept at a temperature of 2.5-3.5 hours, then heated to 45-55°C for 10-15 hours, heated to 75-105°C for 2.5-3.5 hours, and finally cooled to 65-75°C for 1.5-2.5 hours. After the mold is opened, the secondary curing program is heated, kept at 100-120°C for 2-4 hours, and finally cooled to 65-75°C for 1.5-2.5 hours.
[0031] The above curing procedure can also be adaptively adjusted as needed, and the inventor will not elaborate on it here.
[0032] An optical lens material is prepared by adopting the above composition, and the optical lens material has high refractive index and low thermal expansion coefficient.
[0033] According to the test, the optical lens material composition finally obtained by the above preparation method has a refractive index of 1.60 to 1.75, which is suitable for higher-end optical lens materials; the linear expansion coefficient is 25 to 50×10 -6 / ℃, the material's dimensions are more stable, the design is more flexible, and the cost is reduced. DETAILED DESCRIPTION
[0034] The following is a further detailed description of the above contents of the present invention through specific implementation methods in the form of examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Unless otherwise specified, the following examples are all completed using conventional existing technologies. In the following examples, each chemical substance is abbreviated as follows:
[0035] BEPS: bis(β-epithiopropyl) sulfide, BEPDS: bis(β-epithiopropyl) disulfide, AAdH-OH: 3-amino-1-adamantanol, BMMD: 1,4-dithiane-2,5-dimethylthiol, BES: 2,3-bis(2-mercaptoethylthio)-3-propyl-1-thiol, NBDI: norbornane diisocyanate, IPDI: isophorone diisocyanate.
[0036] Example 1
[0037] At 20°C, 0.1g of dibutyl phosphate, 0.1g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 7.5g of IPDI and 2.5g of AAdH-OH. After stirring and dissolving completely, 90g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, wherein the Tg is 125°C, the Nd is 1.6992, and the linear expansion coefficient is 42*10 -6 / ℃.
[0038] Example 2
[0039] At 20°C, 0.1g of dibutyl phosphate, 0.07g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 5g of NBDI and 10g of BMMD. After stirring and dissolving completely, 85g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient. The material has a Tg of 123°C, an Nd of 1.7002, and a linear expansion coefficient of 36*10 -6 / ℃.
[0040] Example 3
[0041] At 20°C, 0.1g of dibutyl phosphate, 0.07g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 9g of NBDI, 3g of AAdH-OH and 13g of BMMD. After stirring and dissolving completely, 75g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, wherein the Tg is 127°C, the Nd is 1.6858, and the linear expansion coefficient is 38*10 -6 / ℃.
[0042] Example 4
[0043] At 20°C, 0.1g of polyoxyethylene ether phosphate, 0.08g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 15g of IPDI, 5g of AAdH-OH and 2g of BES. After stirring and dissolving completely, 68g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, wherein the Tg is 122°C, the Nd is 1.7325, and the linear expansion coefficient is 46*10 -6 / ℃.
[0044] Example 5
[0045] At 20°C, 0.1g of dibutyl phosphate, 0.1g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 7.5g of IPDI and 6.5g of BES. After stirring and dissolving completely, 86g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, wherein the Tg is 120°C, the Nd is 1.6847, and the linear expansion coefficient is 32*10 -6 / ℃.
[0046] Example 6
[0047] At 20°C, 0.1g of dibutyl phosphate, 0.1g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 7.5g of IPDI and 6.5g of BMMD. After stirring and dissolving completely, 86g of BEPDS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, whose Tg is 121°C, Nd is 1.7412, and the linear expansion coefficient is 32*10 -6 / ℃.
[0048] Comparative Example 1
[0049] At 20°C, 0.1g of dibutyl phosphate, 0.07g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 5g of IPDI and 10g of ethanethiol. After stirring and dissolving completely, 85g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 10μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, wherein the Tg is 87°C, the Nd is 1.6520, and the linear expansion coefficient is 75*10 -6 / ℃.
[0050] Comparative Example 2
[0051] At 20°C, 0.1g of dibutyl phosphate, 0.1g of tetrabutylphosphonium bromide, 3.2ppm of blue agent and 1.5ppm of red agent were added to 12g of HMDI and 13g of 1,6-hexanedithiol. After stirring and dissolving completely, 75g of BEPS was added and stirred at 20°C for 30min to obtain a prepolymer liquid. After vacuum degassing for 30min, the prepolymer liquid was filtered through a polytetrafluoroethylene filter membrane with a pore size of 3μm and injected into a mold. The mold was then placed in a programmed temperature curing furnace for curing to obtain an optical lens material with a high refractive index and a linear expansion coefficient, wherein the Tg is 80°C, the Nd is 1.6213, and the linear expansion coefficient is 82*10 -6 / ℃.
[0052] The refractive index, glass transition temperature and linear expansion coefficient of the optical lens materials with high refractive index and low thermal expansion coefficient provided in Examples 1-6 and Comparative Examples 1-2 were tested respectively; the refractive index (ne) was tested by Abbe refractometer; the glass transition temperature (Tg) was tested by DSC-3 differential scanning calorimeter at a heating rate of 10K / min; the linear thermal expansion coefficient was tested by quartz dilatometer method. The test results of each performance are shown in the following table.
[0053]
[0054] As can be seen from the table, the Tg and linear expansion coefficient of the optical lens material with high refractive index and low thermal expansion coefficient provided by Examples 1-6 of the present invention are far superior to the corresponding performance of Comparative Examples 1-2. Due to the higher glass transition temperature, the application range of the material is wider, the service life is significantly improved, and the yield rate is higher, the cost performance is further improved, and the unit cost of the entire processing process is reduced, thereby increasing the profit of the enterprise and being more conducive to industrial production and application. In addition, there is no unstable group that yellows in the product components themselves, the performance is stable after curing, and the user experience is better, which is a significant improvement over the prior art.
[0055] The embodiments disclosed above enable those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composition for an optical lens material with a high refractive index and a low thermal expansion coefficient, characterized in that: The components are as follows by weight: 75 parts of bis(β-epithiopropyl) sulfide, 3 parts of 3-amino-1-adamantanol, 13 parts of 1,4-dithiane-2,5-dimethylthiol, and 9 parts of norbornane diisocyanate.
2. An optical lens material, characterized in that: The composition according to claim 1 is used for preparation.
Citation Information
Patent Citations
Quaternary phosphonium salt modified mercaptan with autocatalytic activity, preparation method and ultrahigh-refractive-index optical resin material prepared from quaternary phosphonium salt modified mercaptan
CN111574563A
High-refractive-index super-tough optical resin material and preparation method thereof
CN113444247A
Composition for resin
JP2007277438A
Template polymerization method of thioepoxy-based optical material, and polymerizable composition thereof
WO2013089538A1